Virtual learning object applied to the teaching process in the subject of physical dducation in students of 3rd year of baccalaureate of the Bolivar High School – Tulcán - Salazar Pazos, Williams Rene; Enríquez Herrera, Jhony Vicente (SATHIRI, 2024)
This article highlights the importance of computing today and its trends in the information society, as well as virtual learning objects (OVA), which can be applied effectively in the teaching process with in Education. As such, a particular virtual learning object Thinglink is analyzed that allows the creation of interactive online content by making it easier for users to add links and tags to images, videos and other digital media to create more interactive learning and exploration experiences. This digital resource allows you to enrich the learning experience by creating interactive images that incorporate multimedia information since you can upload your own images or use images available on the platform and add links to other websites, videos, audio, text and other resources. Online, users can use ThingLink to enhance understanding of concepts, encourage active participation, and provide a dynamic platform for teaching. Therefore, the present research aims to develop an application-oriented online solution as a complement to teaching in the teaching process within the subject of Physical Education in 3rd year Baccalaureate students of the Bolívar Educational Unit of the City of Tulcán. ; In conclusion, the virtual learning object in the field of Physical Education is presented as a versatile tool that will improve the understanding of concepts, facilitate the practice of skills and encourage the active participation of students through interactive visual resources. This innovative approach can transform the way subject knowledge is taught and absorbed.